Can conditional cash transfers improve maternal health and birth outcomes? Evidence from El Salvador's Comunidades Solidarias Rurales - de Brauw, Alan; Peterman, Amber (International Food Policy Research Institute, 2011)
Although conditional cash transfers (CCTs) are traditionally evaluated in relation to child schooling and nutrition outcomes, there is growing interest in specifically examining maternal and reproductive health impacts. However, since data collection is not typically designed to evaluate these outcomes and sample sizes are often limited, there is a lack of rigorous evidence as to whether and through which pathways these effects may be realized. This paper uses regression discontinuity design and a unique implicit threshold to evaluate the impact of El Salvador's CCT program Comunidades Solidarias Rurales on a range of maternal and reproductive health outcomes: (1) prenatal care, (2) skilled attendance at birth, (3) birth in a health facility, and (4) postnatal care, using data collected by the International Food Policy Research Institute and its collaborators from women who entered the program in 2006 and 2007. Results indicate that robust impacts are found on outcomes at time of birth (skilled attendance and birth in facility), while no impacts are found on healthseeking behavior pre- and postbirth (prenatal and postnatal care). Potential impact pathways as well as the implications of these findings for program design are discussed in the conclusion.